The Signaling and Transformation Potency of the Overexpressed HER2 Protein is Dependent on the Normally-Expressed EGFR - Zhou, Xiangdong (2011)
Human epidermal growth factor receptor 2 (HER2) belongs to the EGFR family of receptor tyrosine kinases that comprises four members. As opposed to the other family members, HER2 does not require ligand binding for activation. Hence, HER2 molecules can undergo spontaneous dimerization, autophosphorylation and activation of downstream signaling pathways especially under conditions of overexpression, a commonly encountered phenomenon in breast cancer. In this study, we sought to investigate the mechanism by which HER2 musters signaling and transformation potency. We show that HER2 overexpression per se induces a significant increase in basal mitogenic and cell survival signaling, which was augmented by EGF stimulation. Inhibition of the normally expressed EGFR significantly suppressed the ability of overexpressed HER2 to induce enhanced signaling and cell transformation, suggesting that HER2 requires the EGFR and potentially other members to maximize its signaling and transformation potency. The novel observation revealed by prolonged EGF stimulation studies was the biphasic signaling pattern in the presence of HER2 overexpression that suggested the induction of a short-circuited mechanism, permitting sustained signaling. Our results further show that the short-circuited signaling was due to the re-shuttling of internalized receptor molecules to the Rab11-positive recycling endosomes, while suppressing channeling to the LAMP1-positive lysosome-targeting endosomes. Therefore, HER2’s oncogenicity is dependent, not only on its constitutively active nature, but also on its ability to muster collaborative signaling from family members through modulation of ligand-induced receptor regulation.